Vanillin attenuates oxidative stress and neurochemical balance in MPTP-induced Parkinson’s disease mice by regulating the TLR-4 inflammatory pathway - Gao, Yuan; Liu, Jiang; Wang, Xiaoyan; Meng, Qiang (Folia Neuropathologica, 2024)
This study investigated the protective effect of vanillin against Parkinson’s disease (PD). 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP; 30 mg/kg) was administered s.c. for 6 consecutive days to induce PD and mice were treated with vanillin (100 and 200 mg/kg, p.o.) for 15 days. Cognitive, motor and non-motor functions were assessed to evaluate the effect of vanillin in PD mice. Levels of dopamine and glutamate and activity of monoamine oxidaseB (MAO-B) were estimated in vanillin-treated PD mice. The effect of vanillin on the level of lipid peroxidation and superoxide dismutase in brain tissue of PD mice was estimated. Data of the study revealed that vanillin reversed the altered cognitive, motor and non-motor function in PD mice. Activity of MAO-B and neurochemical level were attenuated with vanillin in PD mice. Inflammatory cytokines, nuclear factor kappa B (NF-kB) and Toll-like receptor 4 (TLR-4) levels were lower in the vanillin-treated group compared to the PD group of mice. Data of the study suggest that vanillin protects against neuronal injury and recovers the altered behaviour in PD mice by regulating neurochemical balance and the TLR-4/NF-kB pathway.